Psychosocial impact of mobility assistive technology on people with neurological conditions - Jimenez Arberas, Estibaliz; Ordoñez-Fernández, Feliciano-Francisco; Rodriguez Menendez, Sergio (Disability and rehabilitation-assistive technology, 2021)
ntroduction: A wide range of products are available to assist mobility, and it is, therefore, of great importance to obtain empirical information regarding the expected impact of the use of these products based on outcome measures. People affected by neurological disorders often use products to assist mobility such as wheelchairs (both manual self-propelled wheelchairs and externally propelled chairs such as electric wheelchairs), walkers, walking sticks, etc. It is important to conduct an assessment of the psychosocial impact of these products on the lives of affected people. Methods: We performed this assessment using the Psychosocial Impact of Assistive Devices Scale (PIADS) and a socio-demographic questionnaire. Results: The results showed greater psychosocial benefits relating to the use of electric wheelchairs in comparison with walking sticks or manual, non-self-propelled chairs. Moreover, significant differences are present in the three subscales of the PIADS in relation to variables such as age, training in the use of assistive technology (AT) and funding. Conclusion: Therefore, we conclude that the use of AT should be promoted among this group as a way to improve their adaptability, competency and self-esteem, and to reduce limits on participation deriving from the physical and contextual barriers faced by this collective.
Keywords: assistive technology; neurological disease; PIADS; mobility; WOS(2); Scopus